Cardiovascular disease and cancer: Evidence for shared disease pathways and pharmacologic prevention. (August 2017) - Masoudkabir, Farzad; Sarrafzadegan, Nizal; Gotay, Carolyn; Ignaszewski, Andrew; Krahn, Andrew D.; Davis, Margot K.; Franco, Christopher; Mani, Arya
Abstract: Cardiovascular disease (CVD) and cancer are leading causes of mortality and morbidity worldwide. Strategies to improve their treatment and prevention are global priorities and major focus of World Health Organization's joint prevention programs. Emerging evidence suggests that modifiable risk factors including diet, sedentary lifestyle, obesity and tobacco use are central to the pathogenesis of both diseases and are reflected in common genetic, cellular, and signaling mechanisms. Understanding this important biological overlap is critical and may help identify novel therapeutic and preventative strategies for both disorders. In this review, we will discuss the shared genetic and molecular factors central to CVD and cancer and how the strategies commonly used for the prevention of atherosclerotic vascular disease can be applied to cancer prevention. Graphical abstract: Image 1 Highlights: Cardiovascular disease (CVD) and cancer are leading causes of mortality and morbidity worldwide. CVD and cancer have common risk factors and shared genetics and molecular mechanisms that are central to their pathogenesis. The shared pathways of CVD and cancer are potential targets for development of novel drugs for joint pharmacologic prevention of CVD and cancer. A growing body of evidence supports a role for aspirin, statins, ACE inhibitors/ARBs, metformin, and TZDs in cancer prevention. Both pharmacologic and non-pharmacologic preventive programs should be directed jointly at CVD and cancer.